The Effect of Body Image and Self-Acceptance on Dieting among Early Adult Women in Fitness Studios - Winadia Warnarana Ardiani; Idha Rahayuningsih (Universitas Negeri Medan, 2026)
Aesthetic pressure in fitness environments often drives early adult women to engage in dieting influenced by psychological dynamics. This study examined the influence of body image and self-acceptance on diet behavior among early adult women in dance studios. Using a quantitative associative approach with a survey design, the study involved 139 women aged 18–40 years from Dewi Dance Studio and La Dinda Club Lamongan through saturated sampling. Data were collected using three psychological scales and analyzed with multiple linear regression using JASP software. Results showed body image and self-acceptance simultaneously influenced diet behavior significantly (F = 10.28; p < 0.001). Partially, body image had a positive effect (β = 0.261; p = 0.001), while self-acceptance had a negative effect (β = −0.261; p = 0.001), contributing 13.1% to diet behavior variance. These findings provide a foundation for readers to critically analyze the shift in dieting motives within fitness environments and the urgency of integrating psychological interventions into fitness programs.